factorise the expression x y z(z square + 6 z- 16) divided 2 Y (Z – 2)

### 2 thoughts on “factorise the expression x y z(z square + 6 z- 16) divided 2 Y (Z – 2)”

### Leave a Comment

You must be logged in to post a comment.

factorise the expression x y z(z square + 6 z- 16) divided 2 Y (Z – 2)

You must be logged in to post a comment.

Answer:I hope it is helpful to you and others. Please mark me as brainliast.

Step-by-step explanation:=

xyz ( z^2 + 6z – 16 )2y ( z – 2 )

=

( z^2 + 8z – 2z – 16 )2y ( z – 2 )

=

xyz [ z ( z + 8 ) – 2 ( z + 8 ) ]2y ( z – 2 )

=

xyz ( z – 2 ) ( z + 8 )2y ( z – 2 )

=

xyz ( z + 8 )2y

=

x × y × z ( z + 8 )2 × y

=

xy(z+8)2## 4yz(z

## 2

## +6z−16)÷2y(z+8)

## 2y(z+8)

## 4yz(z

## 2

## +8z−2z−16)

## z+8

## 2z(z(z+8)−2(z+8))

## ⇒

## (z+8)

## 2z[(z+8)(z−2)]

## 2z(z−2)=2z

## 2

## −4z.